Publiczna usługa hybrydowa jako instrument przeciwdziałania wykluczeniu cyfrowemu i usprawniania ogólnego postępowania administracyjnego – wybrane zagadnienia .......... 131 - Kosicki, Tomasz (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
THE HYBRID PUBLIC SERVICE AS A TOOL TO COMBAT DIGITAL EXCLUSION AND IMPROVE GENERAL ADMINISTRATIVE PROCEDURES – SELECTED ISSUESThe entry into force of the provisions of the Electronic Delivery Act of 18 November 2021 can be seen as a kind of revolution. This is due to the introduction of e-delivery services, which were previously unknown or little known to the Polish legislator. These are the public registered electronic delivery service, the public, hybrid service and the qualified registered electronic delivery service. The cited Act has also influenced the provisions of specific laws, such as the Act of 14 June 1960 – Code of Administrative Procedure, explicitly modifying the principle of the officialness of service contained therein. One of the aims of introducing the indicated services is to address digital exclusion. The drafters have assigned a challenging task to the Public Hybrid Service, which involves converting an electronic document received from a public entity into traditional letter mail. Therefore, the objective of this paper is twofold: to provide a characterization of the Public Hybrid Service and to address whether this service can effectively fulfil the legislator’s goals in addressing digital exclusion. The second objective was to highlight the changes made to the Code’s provisions on service, with particular reference to the conditions and consequences of using the title service in the context of general administrative proceedings.